Historical Reflections on Accountability - Ohmann, Richard (Radical Teacher, 2014)
Imagine that almost all academics think of ourselves as responsible to others, and, if pressed, might allow substitution of "accountable." Responsibility to our employers is contractual, and the professional ethos urges responsibility to students (our clients), to colleagues, and to vague but strong principles of intellectual conduct that obtain in our disciplines. The professional idea calls for responsibility to society as well: we earn our privileges not just by guarding and augmenting our special bodies of knowledge, but by undertaking to put those knowledges to work for the good of all.